Dietary shochu kasu alleviates fatty liver induced by orotic acid - Buang, Yohanes; Ola, Pius D.; Yanagita, Teruyoshi (Bangladesh Journal of Pharmacology, 2010)
<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-hebrew-font-family: 'Times New Roman'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US;" lang="en-US">The effects of dietary shochu kasu (5%) on orotic acid-induced fatty liver were studied in rats<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-hebrew-font-family: 'Times New Roman'; language: en-US; mso-ansi-language: en-US;" lang="en-US">.<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-hebrew-font-family: 'Times New Roman'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US;" lang="en-US"> Liver triglyceride content of orotic acid-fed rats increased by 5-fold in comparison to basal group. Shochu kasu reduced triglyceride content by two-third. The activities of fatty acid synthase and phosphatidate phosphohydrolase significantly decreased that was approximately by 35% and 20%, respectively. The serum lipid levels however were nearly unchanged. The alleviation of fatty liver in rats with shochu kasu<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-hebrew-font-family: 'Times New Roman'; language: en-US; mso-ansi-language: en-US;" lang="en-US">,<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-hebrew-font-family: 'Times New Roman'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US;" lang="en-US"> therefore<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-hebrew-font-family: 'Times New Roman'; language: en-US; mso-ansi-language: en-US;" lang="en-US">,<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-hebrew-font-family: 'Times New Roman'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US;" lang="en-US"> was associated with the inhibition of fatty acid synthase and phosphatidate phosphohydrolase activities<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-hebrew-font-family: 'Times New Roman'; language: en-US; mso-ansi-language: en-US;" lang="en-US">.